Pengaruh Investasi dan Utang Luar Negeri Terhadap Cadangan Devisa Indonesia - Nailil Fitri; Sri Ulfa Sentosa; Melti Roza Adry (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2019)
This research aims to knows and analyze the impact of Indonesia investment abroad, foreign direct investment and external debt to foreign exchange reserve. This research use ordinary least square (OLS). The result from this research is Indonesia investment abroad have significant and negative effect to foreign exchange reserve in indonesia. FDI unsignificant and positive impact to foreign exchange reserve in Indonesia. External debt have significant positive to foreign exchange reserve in Indonesia. From this research can be suggest that government and BI should be notice macro economic condition that impacted to balance of payment an stability of foreign exchange reserve, Indonesia’s government should be fix the resources that will increase FDI and foreign exchange reserve can be accomplish.